‘To Think Seriously about the Relatives Left Behind’: Charity and Widows’ Financial Strategies in the Aftermath of Utrecht’s Cholera Epidemic of 1866 - Tanis, Nelleke (BMGN - Low Countries Historical Review, 2024)
This article studies the ways in which women who were widowed during the cholera epidemic of 1866 in Utrecht tried to cope with the loss of their male breadwinner, as well as the ways in which the wider urban community reacted to their situation. A unique set of 245 questionnaires on the financial situation of these widows and their households allows us to reconstruct the different financial strategies they used to deal with the loss of income, as well as the almost unavoidable result: poverty. The charity initiatives undertaken by Utrecht’s citizenry to support these women show an increasing awareness that poverty lay at the root of the recurring epidemics, and that its alleviation was indispensable for the structural improvement of public health. However, it proved very difficult to bring about such change. Recovery from the crisis meant a return to the status quo, leaving the fundamental problems underlying the outbreak untouched. As a consequence, this research nuances the idea of crises such as epidemics as agents of structural change.